Postural adjustments preceding string release in trained archers - Kuch, A.; Tisserand, R.; Durand, F.; Monnet, T.; Debril, J. F. (Journal of Sports Sciences, 2023)
Optimal postural stability is required to perform in archery. Since the dynamic consequences of the string release may disturb postural equilibrium, they should be integrated into an archer motor programme to optimize postural stability. This study aimed to characterize the postural strategy archers use to limit the potentially detrimental impact of the bow release on their postural stability and identify characteristics that may explain a better performance. Six elite and seven sub-elite archers performed a series of 18 shots at 70 metres, standing on two force plates. Postural stability indicators were computed during the aiming and the shooting phase using the trajectory of the centre of pressure. Two postural strategies were defined, as whether they were triggered before (early) or after (late) the string release time. Both groups used anticipated postural adjustments, but elite archers triggered them before the string release more often and sooner. Scores differed between the two groups, but no differences were found between early and late shots. Trained archers seem to have finely integrated the dynamic consequences of their bow motion, triggering anticipated postural adjustments prior to the string release. However, it remains unclear whether this anticipation can positively influence the performance outcome.